Detection of vibrations defects in gas transportation plant based on input/output data analysis: gas turbine investigations - Djaidir, Benrabeh; Hafaifa, Ahmed; Kouzou, Abdallah; Guemana, Mouloud (Zielona Góra: Uniwersytet Zielonogórski)
In oil and gas industrial production and transportation plants, gas turbines are considered to be the major pieces of equipment exposed to several unstable phenomena presenting a serious danger to their proper operation and to their exploitation.
Keywords: vibrations detection; vibrations control; gas turbines; unstable phenomena; supervision system